2002
DOI: 10.5326/0380458
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis Following Surgical Excision of Canine Cutaneous Mast Cell Tumors With Histopathologically Tumor-Free Versus Nontumor-Free Margins: A Retrospective Study of 31 Cases

Abstract: The purpose of this study was to determine if the presence of histopathologically tumor-free versus nontumor-free margins was prognostic for relapse or tumor-related death in dogs following surgical excision of single or multiple cutaneous mast cell tumors confined to the skin without evidence of metastasis to lymph nodes or other noncutaneous sites. Differences in tumor-related death or frequency of relapse between the two groups were not significant. Failure to achieve histopathological tumor-free margins fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
137
5
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(173 citation statements)
references
References 6 publications
17
137
5
9
Order By: Relevance
“…Tumor recurrence developed in a small number of dogs with completely excised, grade II, cutaneous mast cell tumors [21,27], suggesting that a complete excision can reduce recurrence. In a prior study, the frequency of recurrence in complete surgical excision within 24 months postoperatively was significantly lower than in incomplete surgical excision [13]. These previous findings corresponded with our data.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Tumor recurrence developed in a small number of dogs with completely excised, grade II, cutaneous mast cell tumors [21,27], suggesting that a complete excision can reduce recurrence. In a prior study, the frequency of recurrence in complete surgical excision within 24 months postoperatively was significantly lower than in incomplete surgical excision [13]. These previous findings corresponded with our data.…”
Section: Discussionsupporting
confidence: 82%
“…The frequency of recurrence in the complete surgical excision cases was significantly lower than in incomplete surgical excision during 24 months following surgery [13]. In contrast, the percentage of recurrence of incomplete excision cases of grade II mast cell tumors was only 50% [13], so about 50% of incomplete excision cases did not show recurrence. From these facts, many veterinary practitioners would like other more accurate prognostic factors in incomplete excision cases.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…However, this finding was not noticed in this study, and was also not observed in the study by Miller et al (2014). In a study conducted by Michels et al (2002), the likelihood of recurrence in MCT with evidence of incomplete surgical margins was not higher than those with clean margins. This may be the result of failure in the assessment of the surgical margins, or even by reduced importance of the extent of the surgery in the local control of canine MCT.…”
Section: Discussioncontrasting
confidence: 48%